Estimation of muscle pain based on Twitter data. Issue 6 (5th March 2019) - Okumura, Hiroki; Hayashi, Hitoshi
Abstract : To estimate muscle pain, data from Twitter posts, or tweets, with and without symptomatic remarks were collected using the Twitter API. We performed morphological analysis, weighting by TF‐IDF, and calculation of the cosine similarity between the tweets, and then used the results to estimate muscle pain. Evaluation experiments were conducted to examine whether tweets with symptomatic remarks shared higher cosine similarity among all tweets combined. The results indicate that Twitter data could be used to characterize muscle pain symptoms. © 2019 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.